PENGEMBANGAN APLIKASI BELAJAR MENULIS ALFABET DAN ANGKA UNTUK PERANGKAT MOBILE BERBASIS ANDROID DAN IOS MENGGUNAKAN FRAMEWORK COCOS2 - Kovalevsdeno Al Fajr Amiton; KM. Syarif Haryana; Rohmat Nur Ibrahim (Jurnal Computech & Bisnis (e-Journal), 2015)
This study is about application development of learn how to write alphabet A-Z both uppercase and lowercase letter, number and object word that length is not longer than 5 letters. The application packed into a game where there are images, animations and audio for background music and sound effect. The purpose is to make player not bored while learning how to write. The images theme is colorful, while the audio theme is cheerful. The application was developed for Android and iOS-based device using Cocos2d-x framework that built in C++ language programming. A lot of variations in both Android and iOS device ultimately from screen resolution could become a problem in application development. The solution that was taken is to use a single image that have biggest resolution, so when it’s used into a device which have smaller screen resolution, scaling is used for the image asset. In the development, the player can see hint animation as a guide how to write a letter or number. The writing standard refer to handwritingforkids.com website. The game will be over when the player has finished the writing that fit with the sequence that shown by the hint. The game score will be displayed when the game is over, and the highest score will be saved in the application as a record. The score of the game valued by the player writings. In a level, there are obstacles and checkpoints that placed in certain positions. The checkpoint placed inside of the letter or number line. While the obstacle placed on the outside of the letter or number line. The more the obstacle touched, then the more the player score will decrease.Keywords: cocos2d-x framework; learning application; game education